Resistência de união de cimentos resinosos na dentina afetada por cárie induzida artificialmente - Peixoto, Aline Carvalho (2013)
The bond strength of indirect restorations luted with self-adhesive resin cements to caries affected dentin has been poorly studied, despite this substrate be frequently found in cavity preparations. To standardize this substrate type, in vitro protocols of caries induction under controlled conditions are commonly used for bond strength tests. The aim of this study was to evaluate the bond strength of self-adhesive resin cements RelyX U200 and BisCem, and regular resin cement RelyX ARC to caries-affected dentin induced artificially. A microcosm biofilm from saliva of a donator was inoculated over dentin samples from caries-free human third molars and cultivated under anaerobic conditions for 14 days. It was used a model with intermittent availability of 1% sucrose for 4 hours per day. Cylinders of each resin cement were build-up on sound and caries-affected dentin surface (n=24). The cylinders were submitted to microshear testing after 24 hours. Vicker’s hardness (VH) and elastic modulus (E) were measured in both substrates until the depth of 200 μm. Data of bond strength were submitted to two-way ANOVA followed by Student-Newman-Keuls (SNK) multiple comparisons test; and the failure mode was evaluated by Fisher’s Exact and Chi-Square tests (P < 0.05). Data of VH and E were submitted to split-plot ANOVA and SNK’s test (P < 0.05). Caries-affected dentin presented the lower values of VH and E than sound dentin until the depth of 50 and 100 μm, respectively. The bond strength of all cements was lower on caries-affected dentin than sound dentin. Bond strength of RelyX U200 was similar to RelyX ARC and higher than BisCem, independently of substrate. In conclusion, the resin cements evaluated showed lowest bond strength values to caries-affected dentin, which presented lower mechanical properties than sound dentin near to surface where the adhesive procedures were performed.